Flocs are the main source of nitrous oxide in a high-rate anammox granular sludge reactor: insights from metagenomics and fed-batch experiments. (1st November 2020) - Zhuang, Jin-long; Zhou, Yuan-yuan; Liu, Yong-di; Li, Wei
Highlights: Flocs are the main source of N2 O in high-rate anammox granular sludge reactor. High N2 O level was a result of NO inhibition of N2 O reduction. Anammox bacteria in granules scavenge NO mitigating its impact on N2 O release. Abstract: Nitrous oxide (N2 O) emissions from anammox-based processes are well documented but insight into source of the N2 O emission in high-rate anammox granular sludge reactors (AGSR) is limited. In this study, metagenomics and fed-batch experiments were applied to investigate the relative contributions of anammox granules and flocs to N2 O production in a high-rate AGSR. Flocs, which constitute only ~10% of total biomass contributed about 60% of the total N2 O production. Granules, the main contributor of nitrogen removal (~95%), were responsible for the remaining ~40% of N2 O production. This result is inconsistent with reads-based analysis that found the gene encoding clade II type nitrous oxide reductase ( nosZII ) had similar abundances in both granules and flocs. Another notable trend observed was the relatively higher abundance of the gene for NO-producing nitrite reductase ( nir ) in comparison to the gene for the nitric oxide reductase gene ( nor ) in both granules and flocs, indicating nitric oxide (NO) may accumulate in the AGSR. This is significant since NO and N2 O pulse assays demonstrated that NO could lead to N2 O production from both granules and flocs. However, since anammox bacteria, which were shown to be in higher abundance in granules than in flocs, have the capacity to scavenge NO this provides a mechanism by which its inhibitory effects can be mitigated, limiting N2 O release from the granules, consistent with experimental observation. These results demonstrate flocs are the main source of N2 O emission in AGSR and provide lab-scale evidence that NO-dependent anammox can mitigate N2 O emission. Graphical abstract: Image, graphical abstract